Organizational patterns, rhetorical moves, and diction in Filipino and American presidential campaign blogs (The Scholastican Journal, 2011)
The study aimed to identify the organizational patterns, rhetorical moves and diction in the presidential campaign blogs of a Filipino and American candidate. It was found out that both groups employed the deductive style of writing, enumerated the abilities of the qualities as the most frequently used move, and employed mostly predicate type of diction which may have been attributed to the purpose, audience and the nature of blogs.